Tecnología web en la difusión de información de donación voluntaria de sangre del Banco de Sangre Regional del HOSPITAL II-2-TARAPOTO - García Ramírez, Luis Anthony (2013)
The following research studies the influence of the application of Web technology in improving information spread about voluntary donation of the Regional Blood Bank of Hospital II-2-Tarapoto. As a sample, a part of population of the city of Tarapoto was as a sample. The application of this study divided the sample into two groups, one experimental and other one to control, in the experimental group the stimulus variable web technology was applied, implementing a website with multimedia elements for this purpose, ensuring a homogeneous and significant improvement in the level of knowledge regarding voluntary blood donation in this group, relative to the control group in which the information using traditional media such as brochures, television, etc.. So it is shown that the application of web technology provides better dissemination of voluntary blood donation compared it spread traditional media.